2021
DOI: 10.3758/s13414-021-02382-2
|View full text |Cite
|
Sign up to set email alerts
|

From eye to arrow: Attention capture by direct gaze requires more than just the eyes

Abstract: Human attention is strongly attracted by direct gaze and sudden onset motion. The sudden direct-gaze effect refers to the processing advantage for targets appearing on peripheral faces that suddenly establish eye contact. Here, we investigate the necessity of social information for attention capture by (sudden onset) ostensive cues. Six experiments involving 204 participants applied (1) naturalistic faces, (2) arrows, (3) schematic eyes, (4) naturalistic eyes, or schematic facial configurations (5) without or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Although the present study revealed an interaction between gaze cues and emotion expressions, there was no evidence that gaze and motion cues interacted. This pattern is in line with previous studies with this paradigm (Böckler et al, 2014, 2015; Boyer & Wang, 2018; Breil et al, 2022; van der Wel et al, 2018). Similarly, the effect of sudden onset motion was not modulated by emotion expression in any of the experiments, neither on the level of performance nor in measures of gaze behavior.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the present study revealed an interaction between gaze cues and emotion expressions, there was no evidence that gaze and motion cues interacted. This pattern is in line with previous studies with this paradigm (Böckler et al, 2014, 2015; Boyer & Wang, 2018; Breil et al, 2022; van der Wel et al, 2018). Similarly, the effect of sudden onset motion was not modulated by emotion expression in any of the experiments, neither on the level of performance nor in measures of gaze behavior.…”
Section: Discussionsupporting
confidence: 93%
“…An alternative explanation is that anger and fear are particularly strong and action-related emotions that could override effects of gaze direction, especially when they are presented in a sudden fashion and simultaneous with gaze shifts (Ortony & Turner, 1990;Schupp et al, 2004;Vuilleumier, 2002). Interestingly, sudden onset motion effects were preserved in both experiments, which further points toward the independence of gaze and motion cues (see also Böckler et al, 2014;Breil et al, 2022).…”
Section: Discussionmentioning
confidence: 71%
“…Some researchers consider eye gaze as a unique social cue for attention and have demonstrated different neural mechanisms for attention orienting triggered by social gaze cues and non-social arrow cues [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], since gaze cues can facilitate joint attention. For example, Friesen et al [ 15 ] used a central cueing paradigm to test the differences in attention orienting triggered by eye gaze and arrow cues.…”
Section: Introductionmentioning
confidence: 99%